Highly cross-linked polymeric nanoparticles with aggregation-induced emission for sensitive and recyclable explosive detection. (July 2021) - Liang, Xiaoqin; Wen, Lixin; Mi, Yifang; Guo, Jingjing; Yu, Bang; Tao, Meng; Cao, Zhihai; Zhao, Zujin
Abstract: Aggregation-induced emission (AIE) polymeric nanoparticles (PNPs) are promising candidates for detection of nitroaromatic explosives. However, the major limitation of these AIE PNPs is the complicated synthesis and deteriorated detection accuracy because of the poor colloidal and morphological stability. This study provided a facile method to construct AIE PNPs with highly cross-linked polymer matrix for sensitive and accurate detection of nitroaromatic explosives. The highly cross-linked AIE PNPs with a 50 nm particle size were prepared through copolymerization of divinylbenzene (DVB) and a tetraphenylethene (TPE)-based AIE luminogen, (4′-tetraphenyletheyl)pheny-3-butenylether (TPE-PBE), in a water-borne miniemulsion system. Due to the good aqueous dispersibility and highly cross-linked polymer matrix, the poly(DVB- co -TPE-PBE) NPs showed excellent solvent resistance, and sensitive and accurate detection of nitroaromatic explosives in aqueous systems, especially picric acid (PA). Moreover, a rigid poly(DVB- co -TPE-PBE) film could preserve spherical morphology after coating poly(DVB- co -TPE-PBE) NPs onto various substrates (such as filter paper and glass slide). The high surface area and loose packing of poly(DVB- co -TPE-PBE) NPs offered convenience for 2, 4-dinitrotoluene to diffuse and interact with TPE-PBE units. Therefore, cost-efficient and portable poly(DVB- co -TPE-PBE)-coated test strips and film on glass slides exhibited fast response, strong quenching ability, and reusability in visual detection of liquid and volatile explosives, respectively. Graphical abstract: Image 1 Highlights: Highly cross-linked AIE PNPs were prepared via miniemulsion polymerization. The stable structure of AIE PNPs allows fast response, strong quenching, and reusability for explosive detection. The underlying mechanism for explosive detection by the designed AIE PNPs is proposed. The AIE PNP films can be facilely formed by dipping or spin coating on various substrates.